Cardiorenal Syndrome in Patients with Infective Endocarditis Complicated by Acute Heart Failure - Hanna B. Koltunova; Andriy P. Mazur; Oleksii A. Krykunov; Kostiantyn P. Chyzh; Larysa A. Klymenko (Ukrainian Journal of Cardiovascular Surgery, 2022)
Cardiorenal interaction in acute heart failure (AHF) is becoming an increasingly recognized factor to consider in the management of cardiac surgical patients. Achieving adequate control of water balance and simultaneously preserving kidney function is the goal of the optimal management strategy for patients with AHF. The majority of preoperative hospitalizations to intensive care units in patients with infective endocarditis (IE) are associated with the development of AHF. The term “cardiorenal syndrome” (CRS) is used to define kidney dysfunction on the background of AHF. Due to the lack of clear clinical manifestations of CRS in IE, the diagnosis and treatment of this pathology may be delayed and contribute to the increase in the number of postoperative complications. Recent data, both in basic science and in clinical research, have changed our understanding of CRS. To date, several types of impaired interaction between the kidneys and the heart have been identified.The aim. To study the peculiarities of CRS in patients with IE complicated by AHF.Materials and methods. The basis of this study was the clinical data of 41 patients with active IE who were treated at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from 1/1/2020 to 8/31/2020. In order to study the features of clinical manifestation and the course of CRS, a comparative analysis was conducted based on the history and results of laboratory and instrumental research for the group of patients with IE complicated by preoperative AHF, and patients without clinical manifestations of AHF at the time of hospitalization. For an in-depth study of myocardial damage in heart failure, troponin, NT-proBNP, lactate levels were analyzed; dysfunction of the urinary system was assessed by the level of urea and serum creatinine, the volume of diuresis.Results. A reliable relationship between the levels of NT-proBNP and serum creatinine at the preoperative stage was revealed (p˂0.001), as an indicator of the presence of CRS in patients with IE. In the early postoperative period, signs of CRS persisted in patients with IE complicated by preoperative AHF (serum creatinine 157.0±8.5 μmol/l [p<0.001], NT-proBNP 8214.9±2390.0 pg/ml [p=0.010]). Normalization of kidney function indicators was reported on the day 14 after surgery.Conclusions. Cardiac surgical intervention in patients with IE contributes to reduction of CRS manifestations on the day 14 of the postoperative period.